Hubungan Anemia Pada Kehamilan dengan Kejadian Berat Badan Lahir Rendah - Yizri Novrida; Anisa Ayu Tiara; Rangga Pusmaika (Akademi Kebidanan La Tansa Mashiro, 2020)
Low birth weight has a high risk of developmental backwardness of early growth, developmental delay and death in neonates. The largest contributor to the incidence of LBW in Indonesia is anemia in pregnant women who ranged (50.9%) with the most cause is iron deficiency anemia (ADB). The purpose of this study was to determine the association of anemia in pregnancy with LBW incidence at Dr.Adjidarmo Hospital.This type of research is analytic research with cohort design from medical records at RSUD Dr. Adjidarmo Rangkasbitung in 2016. This study use systematic random sampling techniques and get 122 cases of maternity mothers with history of ANC visit in RSUD Dr. Adjidarmo in 2016. The measuring tool used is the data table. The data analysis used Chi-Square.Found that the majority of LBW occur in maternal women who have a history of anemia of 62.3% using Chi-Square test obtained p-value 0.004 (p 0.05), it can be concluded that there is a relationship between anemia in pregnancy with the incidence of LBW.For health service institutions provide information about the dangers and impact of anemia during pregnancy so as to minimize the birth of infants with low birth weight.